The role of market orientation on the performance of social enterprises - Pinheiro, Paula Sofia Neta Vasconcelos (2019)
Market orientation has been presented as an important predictor of business performance. However, it is presumed to contribute to long-term success, both in commercial and nonprofit enterprises. Similarly, entrepreneurship orientation is a concept that has been widely applied to business firms but has not been empirically tested in social enterprises. Moreover, the literature does not present a widely accepted and tested conceptual model relating entrepreneurship orientation, market orientation and performance, in the realm of social enterprises. In order to fill this gap, this research assesses how these strategic orientations affect social and economic performance in the setting of social enterprises. Structural equation modelling was used as a means to analyze the hypothesized relationships. After testing the model on a sample of 805 Portuguese social enterprises, the findings show that both social entrepreneurship and market orientations significantly impact social performance. The results also indicate that market orientation mediates the effect of entrepreneurial orientation on the performance of social enterprises.